Influence of psychiatric diagnosis on treatment uptake and interferon side effects in patients with hepatitis C. Issue 6 (June 2014) - Wu, Jing Yuan J; Shadbolt, Bruce; Teoh, Narci; Blunn, Anne; To, Caroline; Rodriguez‐Morales, Ilys; Chitturi, Shivakumar; Kaye, Graham; Rodrigo, Kalyana; Farrell, Geoff
Abstract Background and Aim Pegylated‐interferon‐α/ribavirin (PEG‐IFN/RBV) treatment can cure hepatitis C virus (HCV) infection but has frequent neuropsychiatric side‐effects. Patients with pre‐existing psychiatric illness may not be offered therapy. We established prevalence of self‐reported psychiatric comorbidity among HCV‐infected patients in a hospital‐liver clinic, and determined the impact of such diagnoses on uptake and tolerance to PEG‐IFN/RBV. Methods All HCV cases referred for assessment in Australian Capital Territory/surrounding regions April 2004–March 2012 were entered into a clinical database. We conducted univariate and multivariate analyses of variables correlating with uptake of antiviral therapy and frequency of treatment‐related side‐effects. Results Of 773 referred patients, 235 (30%) described pre‐existing psychiatric illness. Among these, 26% received antiviral therapy, compared with 30% of 538 without psychiatric comorbidity. History of depression (usually validated by liaison psychiatry) was associated with higher incidence of treatment‐related neuropsychiatric side‐effects (odds ratio 2.79 [1.35–5.70], P < 0.05) but did not affect treatment outcome. Twenty‐seven patients reported schizophrenia: three (11%) received antiviral therapy, compared with 30% admitting depression and 20% with bipolar affective disorder (all assessed by psychiatrist). In most schizophrenia cases, the reason for not offering antiviral treatment was psychological illness, yet none of five treated (these three plus two others in a psychiatric rehabilitation facility) experienced worsening psychiatric symptoms. Conclusions A history of depression is common with hepatitis C but does not affect initiation of antiviral treatment, despite substantially increased risk of psychiatric side‐effects. In contrast, pre‐existing schizophrenia appears to influence treatment decisions, despite little evidence that PEG‐IFN/RBV exacerbates the psychiatric condition, and well‐supervised antiviral therapy can have good outcomes.